De la oralidad a la escritura: un camino de ida y vuelta en el Cancionero Popular Infantil - Cerrillo, Pedro C.; Sánchez Ortiz, César (Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación, 2012)
We cannot ignore transmission’s changes in traditional children’s lyrics. More than one thousand compositions were collectet from two groups of informants: (4th and 5th of elementary school) and adults (55 years of age or older) in 2000 and 2009: As a result of field work, some important aspects have changed: 1) The place where people learned oral compositions: for adults the places were related to the family or public spaces sucha as the street, in 90% of the cases; while children learned traditional songs mainly at school (40%). 2) The person who sang songs: 7% of the adults learned them from teachers, compared to 23% of the children. 3) The process of loss. The transmissión process has change from oral to written language. Thus, the question that arises here about children’s lyrics transmissión is: whether it will be appropriate or not to teach them at school in order to prevent their loss